Analysis of Three Dimensions of Characters in a Teenager Movie: Mean Girls - Simamora, Diana Aprilia (Humanis; Vol 26 No 3 (2022), 2022)
Using descriptive-qualitative method type of research, the analysis is conducted with a purpose of finding out the true depth of the characters using the three dimensions of characters theory by Lajos Egri which covers the aspects of physiological, psychological and sociological dimension. Having done the analysis, it can be concluded that the character Cady Heron, physically appears to be sexy, nice-looking and genuinely pious girl lives around a positive atmosphere. It all changed when she beg an to hang out with meanest charcater in the movie, Regina George that ingrainly vicious deep inside but she still managed to be idolized by people because of her glamourous life. Phisiologically, Regina is pretty, skinny and dressed georgously. Psychologycally, she is mean, she has way worse personality than what is shown. Sociologically, Regina’s life is dreamed by many girls, she is famous, rich, and living glamorously